ANALISIS PRINSIP DESAIN VISUAL PADA INSTAGRAM @KOMINFOBOGOR UNTUK MENYAMPAIKAN INFORMASI KEPADA PUBLIK - Bainuri, Zaidan Halifz; Bachtiar, Willy (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2025)
The development of social media has encouraged the Bogor City Communication and Information Office to utilize Instagram as a means to convey information through visual content. This study aims to describe how visual design principles such as unity, balance, rhythm, and emphasis are applied in the content of @kominfobogor uploads. This study uses a qualitative approach with content analysis techniques and purposive sampling of uploads from January to April 2025. The results of the analysis show that uploads on the @kominfobogor account have optimally applied visual design principles, such as the feed designs "Kantong Parkir Balkot Ramadhan Fest 2025", "Good Friday 2025", and so on. However, some content was still found to have not been optimal in applying visual design principles. Key Word: Visual design principles, Public Communication, Social Media